Lipoma of the Thumb: Spindle Cell Subtype - Johnny El Rayes; Roula Bou Sader; Elie Saliba (Case Reports in Orthopedics)
We report hereby the case of a 61-year-old man who presented with a soft-tissue swelling on the palmar aspect of the thumb. A detailed clinical examination followed by ultrasonography and excisional biopsy confirmed a spindle cell lipoma. Lipomas are rare in the hand and exceptional in the fingers, and we report, to our knowledge, the first spindle cell lipoma in the thumb to help in the differential diagnosis of a similar swelling.